Analysis of the Effect of Career Development Policy and Work Motivation on Employee Productivity and Job Satisfaction Level in Service Companies in Indonesia - Haslindah, Andi; Arisanti, Ivon; Suardi, Suardi; Mardikawati, Budi (West Science Interdisciplinary Studies, 2023)
This study investigates the dynamic interaction between career development policies, work motivation, and employee outcomes in service companies in the Indonesian context. Using a quantitative approach, this study employed Structural Equation Modeling with Partial Least Squares (SEM-PLS) to analyze survey data from 158 employees. The measurement model robustly validated the constructs, revealing significant relationships. Career development policies emerged as a key driver of work motivation, which in turn influenced productivity and job satisfaction. The structural model achieved a good fit index, confirming its validity. This study underscores the critical role of strategic human resource management, offering actionable insights for organizations aiming to optimize employee development, motivation, and overall well-being.